The role of servant leadership in creating a positive school climate - Osias Kit T. Kilag; Felix M. Diano, Jr.; Marsha H. Malbas; Debra P. Mansueto; Se P. Villar; Mervin T. Arcillo (Science and Education, 2023)
This study investigates the role of servant leadership in creating a positive school climate. A quantitative research design was used to examine the relationship between servant leadership and school climate, including the effects of servant leadership on student academic achievement, teacher job satisfaction, and school culture. The study was conducted in several schools in a particular district, and data were collected using a survey questionnaire from 40 teachers and 1000 students. Data were analyzed using descriptive and inferential statistics. The findings suggest that there is a significant positive correlation between servant leadership and teacher job satisfaction (r = 0.55, p < 0.01), school culture (r = 0.62, p < 0.01), and academic achievement (r = 0.45, p < 0.01). The results indicate that servant leadership practices contribute to the development of a positive school climate. The study provides support for the notion that servant leadership is a viable leadership approach in schools that can contribute to the development of a positive school climate. The results suggest that schools should consider implementing servant leadership practices as a way of improving teacher job satisfaction and school culture. By prioritizing the needs of their followers and creating a supportive environment, servant leaders can contribute to the development of a positive school culture that fosters growth and development for teachers and students alike. However, the study had several limitations, including the limited sample size and the reliance on self-reported data. Future research should aim to address these limitations by conducting longitudinal studies with larger and more diverse samples. Overall, this study highlights the importance of servant leadership in creating a positive school climate, and provides important insights for school leaders and policymakers seeking to improve the quality of education in their schools.